Two cases of nephrogenic adenoma in the bladder diverticulum - Tanase, K (Hinyokika kiyo. Acta urologica Japonica, 2000)
We report two cases of a nephrogenic adenoma in the bladder diverticulum. The first patient was an 81-year-old man with gross hematuria. Cystoscopy revealed bladder diverticulum and a papillary tumor within. Bladder diverticulectomy was performed and the histopathological diagnosis was a nephrogenic adenoma. The second patient was a 50-year-old man with gross hematuria and dysuria. Transabdominal ultrasound revealed bladder diverticulum. Transurethral coagulation of the bladder diverticulum was performed. Then three papillary tumors were detected, and were resected transurethrally. The histopathological diagnosis was a nephrogenic adenoma. These are the first and second cases of a nephrogenic adenoma in the bladder diverticulum reported in Japan